In situ Quantitative Analysis of Chemical Composition of Lithium and Beryllium Minerals by Laser Ablation Inductively Coupled Plasma-Mass Spectrometry - Chenzi FAN; Dongyang SUN; Linghao ZHAO; Jihai YUAN; Mingyue HU; Ming ZHAO (Yankuang ceshi)
Lithium and beryllium are the strategic key metals and the minerals such as spodumene and beryl are the main raw materials for extracting lithium and beryllium elements. In order to accurately analyze the minerals by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), the quantitative analytical procedure needs to be improved to reduce the matrix effect caused by non-matrix matching calibration. In the research, a New Wave 193nm ArF excimer laser and an Element Ⅱ high resolution inductively coupled plasma-mass spectrometer were used and the working parameters of the instrument optimized. The analytical results show that Li and Be light elements can quantitatively be determined by the suggested method. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202305310072.